(3GdLGeY GdcHjQ aj UfGYI GdefXhe ef GdcdGe hGdefKhQs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ,J (B630 (3g` s
(3ChdgG (B:s
(3CeG HYO adeG cGf (B[(3JCdja(B] (3GdcdGe s
(3BNQgG (B:s
(3CKfGA aUd CeG JbOje NHQ GdeHJOC Ydjg s
(3GdfSNI HgG MhGTs
(3HgG SJI JbjjOGJ Yf HgGA GdOjf Hf GdfMGS GdMdHis
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B571s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(1637) s
Keywords: (3GdHdGZIs